Pengaruh Terapi Musik Langgam Jawa Terhadap Tingkat Kecemasan Pada Pasien Pre Operasi di RSUD Dr. Soehadi Prijonegoro Sragen - Alfia Dyah Permata; Arina Maliya (Universitas Malahayati Lampung, 2024)
ABSTRACT Music therapy has long been recognized for its potential to reduce anxiety levels in various medical conditions. Preoperative anxiety can negatively impact patients' psychological and physical well-being, as well as surgical outcomes. This study aims to investigate the effects of Javanese Langgam music therapy on preoperative anxiety levels among patients at RSUD Dr. Soehadi Prijonegoro Sragen. This research method is pre-experimental design with one group pre-test and post-test design. The sampling technique in this study used purposive sampling, with 5 respondents and used the Hamilton Anxiety Rating Scale (HARS) questionnaire. The data analysis used in this research was the Wilcoxon test. Based on the results, it was found that there was a significant influence of Javanese nyidam sari music therapy on the level of anxiety in preoperative patients (p=0.043 0.05). It can be concluded that there is an influence of the Javanese style of nyidam sari music therapy on the anxiety level of pre-operative patients in the hospital. Dr. Soehadi Prijonegoro Sragen. Keywords: Music Therapy, Javanese Style, Anxiety ABSTRAK Terapi musik telah lama diakui memiliki potensi untuk mengurangi tingkat kecemasan pada berbagai kondisi medis. Kecemasan sebelum operasi dapat berdampak negatif pada kesejahteraan psikologis dan fisik pasien, serta pada hasil operasi. Penelitian ini bertujuan untuk mengetahui pengaruh terapi music langgam jawa nyidam sari terhadap kecemasan pada pasien pre operasi di RSUD. dr. Soehadi Prijonegoro Sragen. Metode penelitian ini adalah pre eksperimen design dengan one group pre – test dan post – test design. Teknik pengambilan sampel pada penelitian ini menggunakan purposive sampling, dengan 5 responden dan meggunakan kuisioner Hamilton Anxiety Rating Scale (HARS). Analisa data yang digunakan pada penelitian ini adalah uji Wilcoxon. Berdasarkkan hasil didaptakan ada pengaruh signifikansi terapi music langgam jawa nyidam sari terhadap tingan kecemasan pada pasien pre operasi (p=0,043 0,05). Dapat disimpulkan terdapat pengaruh terapi music langgam jawa nyidam sari terhadap tingkat kecemasan pasien pre operasi di RS. dr. Soehadi Prijonegoro Sragen. Kata Kunci: Terapi Music, Langgam Jawa, Kecemasan